The effect of lanthanum carbonate on the flame retardancy and thermal stability of soft PVC materials - Zhuang, Weijing; Zheng, Dan; Hong, Lin (Journal of physics. Conference series, 2025)
In order to investigate the effect of lanthanum carbonate (La 2 (CO 3 ) 3 ) on the flame retardancy and thermal stability of PVC, La 2 (CO 3 ) 3 was first prepared by the precipitation method. Then, La 2 (CO 3 ) 3 was added to soft PVC by the melt blending method. The flame retardancy and thermal stability of the composite material containing La 2 (CO 3 ) 3 PVC were studied using a critical oxygen index analyzer, a building material flammability experimental device, a microcomputer automatic calorimeter, and other instruments. The test results showed that when the mass ratio of PVC to La 2 (CO 3 ) 3 was 20:1, the ultimate oxygen index of soft PVC increased from 24.2% to 27.8%. When the mass ratio of PVC to La 2 (CO 3 ) 3 is 40:1, the vertical combustion grade of soft PVC increases from V-2 to V-1, and with the increase of La 2 (CO 3 ) 3 addition ratio, the vertical combustion grade of the composite material increases to V-0. As the amount of La 2 (CO 3 ) 3 added increases, the unit heat release of PVC composite materials shows a decreasing trend, and the thermal stability is significantly improved. A series of experiments have shown that lanthanum carbonate, as a rare earth flame retardant, can be added to soft PVC to enhance its flame retardant properties and thermal stability, and has a good flame retardant effect.